2019
DOI: 10.1111/jrh.12348
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality in Association With Rural Coal Mining and Combustion in New South Wales Australia

Abstract: Purpose Rural areas may face under‐recognized threats to air quality. We tested 2 hypotheses that 1) rural areas in New South Wales, Australia, would have better air quality than metropolitan Sydney, and that 2) the rural Upper Hunter region characterized by coal mining and coal combustion would have worse air quality than other rural areas of the state. Methods We analyzed 2017 daily mean values for New South Wales, Australia, for particulate matter (PM2.5 and PM10), sulfur dioxide (SO2), nitric oxide (NO), n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Emissions of NOx, particulate matter, and metals were significantly higher from coal mining sites than from other types of NPI sites. This air pollution affects community populations in the vicinity of mining sites, as estimated by emissions data from the NPI in the current study; by the results of our limited analysis of PM10 levels from community monitors; and as estimated by data from stationary community-based air quality monitors as previously reported [14]. PM10 emissions from coal mining sites are particularly noteworthy, accounting for over 42% of national PM10 emissions in the NPI database, but pollution from PM2.5, metals, and nitrogen oxides are also significant.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Emissions of NOx, particulate matter, and metals were significantly higher from coal mining sites than from other types of NPI sites. This air pollution affects community populations in the vicinity of mining sites, as estimated by emissions data from the NPI in the current study; by the results of our limited analysis of PM10 levels from community monitors; and as estimated by data from stationary community-based air quality monitors as previously reported [14]. PM10 emissions from coal mining sites are particularly noteworthy, accounting for over 42% of national PM10 emissions in the NPI database, but pollution from PM2.5, metals, and nitrogen oxides are also significant.…”
Section: Discussionsupporting
confidence: 68%
“…Surface mining in particular contributes to local air pollution [7][8][9], with documented genotoxic effects [8] and increased risks for cancer, cardiovascular disease, and respiratory disease, among community populations [10][11][12][13]. A recent study in Australia reported that air quality as measured by sulfur dioxide (SO 2 ), nitrogen oxides (NOx), or particulate matter with aerodynamic diameter ≤ 10 micrometers (PM10) or ≤2.5 micrometers (PM2.5) was significantly elevated in coal mining regions of New South Wales compared to other parts of the state [14].…”
Section: Introductionmentioning
confidence: 99%
“…Comparatively less discussed, however, are the more localized air pollution implications of fossil fuel extraction and electricity generation. This entails a multiplicity of effects, starting from the air pollution impacts of coal, oil and gas resource recovery (Ghose and Majee, 2000), with Hendryx et al (2019) arguing in favour of considering ‘both urban and rural sources of pollution in air quality studies, and appropriate policy steps to address likely rural air pollution from coal mining’ (p. 518). Gas flaring, for example, has been identified as a major contact point between energy activities and ambient air, by acting as ‘a prominent source of VOCs, CO, CO2, SO2, PAH, NOX and soot (black carbon), all of which are important pollutants which interact, directly and indirectly, in the Earth’s climatic processes’ (Fawole et al, 2016: 182).…”
Section: Nexus Technologies: Tracing the Connections Among Energy And...mentioning
confidence: 99%
“…Research evidence from the United States and other countries indicates that surface coal mining generates air, soil, and water pollution and likely harms the health of nearby populations (3,10,22,57,59,96,112,150). Much of the research in the United States has been conducted on a form of surface coal mining that takes place in Appalachia called mountaintop removal (MTR) (see the sidebar titled Mining in Appalachia).…”
Section: Case Study: Mountaintop Removalmentioning
confidence: 99%